2012
DOI: 10.1172/jci60498
|View full text |Cite
|
Sign up to set email alerts
|

FAM83A confers EGFR-TKI resistance in breast cancer cells and in mice

Abstract: Breast cancers commonly become resistant to EGFR-tyrosine kinase inhibitors (EGFR-TKIs); however, the mechanisms of this resistance remain largely unknown. We hypothesized that resistance may originate, at least in part, from molecular alterations that activate signaling downstream of EGFR. Using a screen to measure reversion of malignant cells into phenotypically nonmalignant cells in 3D gels, we identified FAM83A as a candidate cancer-associated gene capable of conferring resistance to EGFR-TKIs. FAM83A over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
187
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(205 citation statements)
references
References 58 publications
11
187
0
Order By: Relevance
“…In fact, Lee et al demonstrated that FAM83A can activate both MAPK and PI3K-AKT signaling (9). Upon analysis of GFP-and FAM83B-expressing cells stimulated with EGF, we also noted prolonged AKT and EGFR phosphorylation, similar to our observation of MAPK signaling (Supplemental Figure 13).…”
Section: Figuresupporting
confidence: 88%
See 2 more Smart Citations
“…In fact, Lee et al demonstrated that FAM83A can activate both MAPK and PI3K-AKT signaling (9). Upon analysis of GFP-and FAM83B-expressing cells stimulated with EGF, we also noted prolonged AKT and EGFR phosphorylation, similar to our observation of MAPK signaling (Supplemental Figure 13).…”
Section: Figuresupporting
confidence: 88%
“…Interestingly, Lee et al have identified another FAM83 member, FAM83A, based on its ability to confer resistance to EGFR-TKIs in a forward genetics cDNA library screen (9). Similar to their findings, we found that FAM83B-expressing cells had sustained ERK1/2 phosphorylation and enhanced proliferation in the presence of EGFR-TKIs (AG1478, erlotinib, and CL387785) compared with control cells (Figure 6, C and D, and Supplemental Figure 8).…”
Section: Figuresupporting
confidence: 88%
See 1 more Smart Citation
“…Several of these themes are highlighted by articles appearing in the current issue of the JCI, in which two groups, using related approaches, focused on members of the family with sequence similarity, members A and B (FAM83A and FAM83B) (7,8). Although differences between these reports clearly exist, the findings and conclusions of these groups exhibit marked similarities and suggest that these genes may contribute both to the pathophysiology of breast cancer as well as to resistance to EGFR inhibitors.…”
Section: Oncogenic Potentialmentioning
confidence: 99%
“…Therefore, the blockade of EGFR has been validated as an effective approach for cancer therapy. Unfortunately, EGFR-tyrosine kinase inhibitor (EGFR-TKI) therapy has been impeded by resistance [8,9] . Thus, it is important to explore effective means of characterizing patterns of resistance over time and to optimize treatment to prevent or at least prolong the time to EGFR-TKI resistance.…”
Section: Introductionmentioning
confidence: 99%